The Interplay Between Systemic Inflammatory Factors and MicroRNAs in Age-Related Macular Degeneration - Litwińska, Zofia; Sobuś, Anna; Łuczkowska, Karolina; Grabowicz, Aleksandra; Mozolewska-Piotrowska, Katarzyna; Safranow, Krzysztof; Kawa, Miłosz Piotr; Machaliński, Bogusław; Machalińska, Anna (Frontiers in Aging Neuroscience, 2019)
We aimed to explore the expression of systemic inflammatory factors and selected intracellular miRNAs that regulate inflammatory signaling pathways potentially involved in age-related macular degeneration (AMD) pathogenesis. A total of 179 patients with wet AMD, 175 with dry AMD and 121 controls were enrolled in the study. Soluble inflammatory factors were analyzed in plasma samples using Luminex technology. Expression of selected miRNAs was analyzed in isolated nucleated peripheral blood cells (PBNCs) using real-time qPCR. Wet AMD was an independent factor associated with higher concentrations of IL-6 (β=+0.24, p=0.0004), GM-CSF (β=+0.31, p<0.001), IFN-γ (β=+0.58, p<0.001), higher expression of miRNA-23a-3p (β=+0.60, p<0.0001), miRNA-30b (β=+0.32, p<0.0001), miRNA-191-5p (β=+0.28, p<0.0001) and lower concentration of IL-1β (β=-0.25, p=0.0003), IL-5 (β=-0.45, p<0.001), IL-10 (β=-0.45, p<0.001), IL-12 (β=-0.35, p<0.001), lower expression of miRNA-16-5p (β=-0.31, p< 0.0001), miRNA-17-3p (β=-0.18, p=0.01), miRNA-150-5p (β=-0.18, p=0.01) and miRNA-155-5p (β=-0.47, p< 0.0001). Multivariate analysis revealed that dry AMD was an independent factor associated with higher concentration of GM-CSF (β=+0.34, p<0.001), IL-6 (β=+0.13, p=0.05), higher expression of miRNA-23a-3p (β=+0.60, p<0.0001), miRNA-126-3p (β=+0.23, p=0.0005), miRNA-126-5p (β=+0.16, p=0.01), miRNA 146a (β=+0.14, p=0.03), and mRNA191-5p (β=+0.15, p=0.03) and lower concentrations of TNF-α (β =+0.24, p=0.0004), IL-1β (β=-0.39, p<0.001), IL-2 (β =-0.20, p= 0.003), IL-5 (β=-0.54, p<0.001), IL-10 (β=-0.56, p<0.001), IL-12 (β=-0.51, p<0.001), lower expression of miRNA-16-5p (β=-0.23, p= 0.0004), miRNA-17-3p (β=-0.20, p= 0.003) and miRNA-17-5p (β=-0.19, p= 0.004). Negative correlations between visual acuity and WBC, lymphocyte count, TNF-α, IL-1 β, IL-2, IL-4, IL-6, IL-10 concentrations and miRNA-191-5p, as well as positive correlations between visual acuity and miRNA-126-3p, -126-5p, and -155-5p PBNCs expression were found in AMD patients. No such correlations were found in the control group. Our results may suggest the role of both intra- and extracellular mechanisms implicated in inflammatory response regulation in multifactorial AMD pathogenesis.